Rheological behaviour of aqueous montmorillonite dispersions from the tagansky deposit - B. V. Pokidko; M. Yu. Pletnev; M. M. Melnikova (Тонкие химические технологии)
The article considers results of rheological studies of dilute aqueous dispersions of montmorillonite near the sol-gel transition. Results of dynamic light scattering, rotational viscometry, and adsorption data reveal the presence of a critical concentration of the structure formation, which is strongly influenced by the electrolyte (NaCl) concentration in the dispersion. Bentonite dispersion behaves differently with respect to the NaCl content near the critical concentration just before and after it. When we have a smaller particle concentration in the dispersion, extreme dependence of the strength and viscosity characteristics on the NaCl concentration is evident, while monotonic dependence exists at high particle concentration up to attaining the maximal value of the gel tensile strength. The critical concentration obtained from viscometry data is close to the theoretical value obtained for the simplified model in the approximation of hard spheres.